Survey of the physiological races of the oat leaf rust (Puccinia coronata var. avenae) that occur in South Brazil - Coelho, Elisa Thomaz (Pesquisa Agropecuaria Brasileira, 2014)
Samples of the oat leaf rust (Puccinia coronata Cda. var. avenae Frazer & Led), collected from 1959 to 1069 in several South Brazilian localities gave, 1,280 isolations, in which races 201, 202, 203, 205, 207, 211, 213, 216, 226, 227, 230, 233, 234, 236, 237, 238, 249, 258, 263, 265, 272, 274, 276, 277, 278, 279 and 287 were determined. Races 211, 227, 230, 234, 272, 274, 276, 277, 278, 287 were identified in Brazil for the first time. At present the most frequent race is 263, found in more than 50% of the isolations.